THE USE OF MASS MEDIA IN THE WINNING STRATEGY OF THE GOLONGAN KARYA PARTY IN NORTH SUMATERA PROVINCE IN THE 2024 LEGISLATIVE GENERAL ELECTIONS - Ara Auza; Bimby Hidayat; Fuad Putera Perdana Ginting; Mulyadi; M. Rizwan (RADJA PUBLIKA, 2025)
This study aims to comprehensively examine the utilization of mass media as a winning strategy for the Golongan Karya Party (Golkar) in the 2024 Legislative Elections in North Sumatera Province. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with informants consisting of leaders of the North Sumatera Golkar Provincial Board, communication and media teams, district/city branch leaders, elected legislative candidates, and mass media journalists. Data were also obtained through observation and documentation studies of campaign materials, internal party documents, and mass media coverage. Data analysis used the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing. The study found that North Sumatera Golkar Party implemented a multiplatform political communication strategy that synergistically integrated conventional media (radio, newspapers) and digital media (Instagram, TikTok, Facebook, YouTube, WhatsApp). This strategy was built through a systematic strategic planning process using SWOT analysis. Moreover, effective coordination among various levels of party structure and integration of media campaigns with field campaigns created synergy that strengthened campaign impact. This research concludes that, mass media, particularly digital media, played a strategic and significant role in Golkar Party's electoral success in North Sumatera in the 2024 Election. However, the effectiveness of mass media communication strategies did not work in isolation but was integrated with other political strategy elements such as party leadership such as Musa Rajekshah as chairman of the Golkar DPD North Sumatera, legislative candidate quality, relevant programs, and grassroots campaigns.